Investigation of Pesticide Residue Limits in the Surface Water, Case study: Alara Stream in Alanya - Hasan Koçyiğit; Firdevs Sinanoğlu (Doğal Afetler ve Çevre Dergisi)
Recently, the development of industrial activities and technologies, on the one hand make the human life easier, on the other hand, it decreases the available water resources due to environmental pollution. One of the most important environmental pollutants, together with the advancing industrialization and technology, is the widely used of pesticides in agricultural activities. Pesticides, which are indispensable in modern agricultural activities, are used in many areas, like industrial, domestic etc. The main objective of this study is to investigate the pesticide residue in the waters of Alara Stream, which is considered the most important water resource and heartland of Alanya and its environs. The intensity of agricultural activities in the region is very important for the investigation of the pesticide residue. For this purpose, 4 sampling points were determined on the Alara Stream. Samples were collected from these points to represent the wet and dry seasons in this area. The residual levels of 110 pesticides were investigated in the samples. During the selection of these pesticides, the desired parameters in the export of fresh vegetables and fruits are taken into consideration. These parameters are given in Table-4 and Table-5 of the Surface Water Quality Regulation. The samples were extracted according to the Quechers Method and analysed by using the LC-MSMS and GC-MS. Detection and Determination Limits and Recovery studies were carried out during the analysis process. The Detection Limits (LOD) range between 0.23 and 9.67 ppb. According to the results of the analysis, it was observed that the determined pesticide values were lower than these determination limits.